HUBUNGAN KEYAKINAN DIRI DENGAN NYERI TENSION TYPE HEADACHE PADA PASIEN HIPERTENSI DI PUSKESMAS PALARAN - Sanritamaya, Musdalifah Rara; Wibowo, Thomas Ari; Muflihah, Ulfatul (Jurnal Perawat Indonesia, 2024)
Hypertension is a major risk factor contributing to mortality in Indonesia, while tension type headache (TTH) is commonly found in hypertensive patients. One of the factors believed to influence the intensity of TTH pain is self-efficacy, which refers to an individual's belief in their ability to manage their health condition. This study aims to analyze the relationship between self-efficacy and TTH pain in hypertensive patients at Puskesmas Palaran, Samarinda. The study used a quantitative approach with a cross-sectional design, involving 170 hypertensive patients selected through purposive sampling. Data were collected using questionnaires, which included the self-efficacy scale and the TTH pain scale, and analyzed using Pearson correlation with a significance level of 0.05. The results showed a significant negative correlation between self-efficacy and TTH pain (p-value = 0.001; p < 0.05) with a correlation coefficient of -0.383. This indicates that the higher the level of self-efficacy in hypertensive patients, the lower the level of TTH pain experienced. Based on these findings, it is recommended to develop interventions focused on increasing self-efficacy in hypertensive patients. Health education programs aimed at enhancing patients' confidence in managing their hypertension could potentially reduce TTH symptoms and improve the patients' quality of life.